Assessing the response of odonates (dragonflies and damselflies) to a tropical urbanization gradient. Issue 1 (21st December 2020) - Jere, Arjit; Darshetkar, Apeksha; Patwardhan, Ankur; Koparde, Pankaj
Abstract: Understanding species responses to urbanization is important to realize their specific conservation needs. Odonates (dragonflies and damselflies) are freshwater insects perceived as good ecological indicators. To investigate responses of tropical odonates to an urbanization gradient, we sampled adult odonates along an urbanization gradient at six sites along the Mula River across Pune City, Maharashtra, India. For species–habitat analysis, we first performed a variable reduction using principal component analysis. we analyzed species–habitat data using redundancy analysis and canonical correspondence analysis. We documented 15 odonates across 6 sites. Our statistical analyses on patterns of odonate assemblages across sites and environmental variables did not return significant results. However, we detected site-exclusivity in a few species based on occurrence data and identified urban sensitive, urban tolerant and generalist species. We found that the odonate diversity was highest at a moderately urbanized site. We believe that increase in diversity due to moderate amounts of disturbance can be explained by the intermediate disturbance hypothesis. Based on our data, we suggest that for the conservation of odonates in the urban context, anthropogenic disturbance needs to be regulated. Here, we demonstrate that understanding species–habitat associations is the first step towards understanding their ecological and conservation requirements. To conserve odonates and rivers in metropolitan cities like Pune, restoring original river-side habitat and reducing the disturbance at highly urbanized sites to at least intermediate levels needs to be done on an urgent basis.